Human Resource Competency Development Strategy in Msmes in the Digital Era: a Qualitative Study of Jooce Micro-Enterprise in Balunijuk - Mustika Mustika; Nezha Salwa; Muhammad Riski; Ravi Nursetiadi (Jurnal Multidisiplin Sahombu, 2026)
Current digital technology advancements require micro-businesses to adapt and develop their human resource (HR) competencies to compete in the modern era. This study aims to determine HR competency development strategies at the Jooce micro-business located in Balun Ijuk, Bangka Belitung. The research approach used was qualitative, with direct interviews with the business owner and employees serving as the primary data source. The research results show that Jooce has implemented various forms of digital technology, such as the use of a cashless payment system (QRIS), app-based financial records, and promotions through social media platforms like TikTok, Instagram, and WhatsApp Business. The human resource development process is carried out independently through direct guidance from the owner and informal learning from social media, especially TikTok, to keep up with sales trends and product innovations. However, no formal training has been provided specifically. Obstacles faced include a less strategic business location and the lack of a signboard, which makes the business difficult for new customers to find. Overall, Jooce's HR competency development strategy emphasizes independent learning, good communication between owners and employees, and the simple yet effective application of digital technology. The use of social media has been shown to have a positive impact on increasing customer base, especially after their promotional content went viral. The results of this study are expected to serve as a reference for other MSMEs in developing digital-based HR competencies to adapt to the demands of the modern era.